The relationship between American popular culture and some selected aspects of consumer behaviour : a study of Malaysian adolescents / Zailin Zainal Ariffin. - Zailin, Zainal Ariffin (2011)
People’s consumption patterns are subject to a range of influences and youth are no different in this respect. Globalization creates an explosion of products and images for consumers to choose from. In consequence, one is left with questions concerning how young consumers construct meaningful identities and how strategies may be evoked as lifestyles and subculture fragment. This study endeavours to explain the impact of American Popular Culture on the behaviour of Malaysian adolescents as well as to determine the impact of popular music as the prominent source of American Popular Culture. This is done to understand the influence of American Popular Culture on Malaysian adolescents’ consumption patterns. The pervasiveness of American popular culture through out the world can be seen through extensive reports in all printed and electronic media. However, there are gaps in the body of knowledge investigating the impact of popular culture on the consumption patterns of adolescents. The current study includes the following consumption patterns: conspicuous consumption, price sensitivity, brand sensitivity, fashion consciousness and music television exposure. The reviewed literature points to the existence of significant relationships between American Popular Culture and consumption patterns. Furthermore, the literature indicated that a positive relationship exists between conspicuous consumption, brand sensitivity, fashion consciousness and music television exposure, while a negative relationship prevails between American Popular Culture and price sensitivity. Using self-administered questionnaires, a survey was conducted in four major geographical areas in Peninsular Malaysia, i.e., Northern, Southern, Central and Eastern region. In total 1200 questionnaires were distributed, 900 were received within two months period. However, about 820 adolescents between the ages of 16 and 19 years completed all the questions. The Simple Linear Regression and Hierarchical Regression were employed to test the six hypotheses of the study, including the moderating affects of religiosity, gender, ethnicity, family income level and primary education streams on the relationship between American popular culture and five selected areas of consumer behaviour. The results indicated that four out of five hypotheses for direct relationship between independent and dependent variables showed significant relationships. The relationship between American popular culture and price sensitivity was found significant but in the opposite direction. All moderating variables indicated mixed findings. Religiosity showed a moderating effect towards all relationships except American music television exposure. In terms of gender, the results showed a moderating effect on all relationships except price sensitivity and American music television exposure. Furthermore, ethnicity showed a moderating effect towards fashion consciousness but partially supported hypotheses for conspicuous consumption, brand sensitivity and American music television exposure. All family income levels integrations showed significant results as moderator except for conspicuous consumption and price sensitivity. Lastly, the primary education streams indicated four out of five hypotheses with partially supported results.